New EST-SSR Markers for Individual Genotyping of Opium Poppy Cultivars (Papaver somniferum L.) - Vašek, Jakub; Čílová, Daniela; Melounová, Martina; Svoboda, Pavel; Vejl, Pavel; Štikarová, Radka; Vostrý, Luboš; Kuchtová, Perla; Ovesná, Jaroslava (Plants (Basel, Switzerland), 2019)
High-quality simple sequence repeat (SSR) markers are invaluable tools for revealing genetic variability which could be utilized for many purposes, such as breeding new varieties or the identifying current ones, among other applications. Based on the analysis of 3.7 million EST sequences and 15 genomic sequences from bacterial artificial chromosome (BAC) libraries, 200 trinucleotide genic (EST)-SSR and three genomic (gSSR) markers were tested, where 17 of them fulfilled all criteria for quality markers. Moreover, the reproducibility of these new markers was verified by two genetics laboratories, with a mean error rate per allele and per locus equal to 0.17%. These markers were tested on 38 accessions of Papaver somniferum and nine accessions of another five species of the Papaver and Argemone genera. In total, 118 alleles were detected for all accessions (median = 7; three to ten alleles per locus) and 88 alleles (median = 5; three to nine alleles per locus) within P. somniferum alone. Multivariate methods and identity analysis revealed high resolution capabilities of the new markers, where all but three pair accessions (41 out of 47) had a unique profile and opium poppy was distinguished from other species.
Keywords: microsatellites; individual genotyping; Papaver somniferum L.; EST-SSR; Papaveraceae